Post-stabilization politics in Latin America : competition, transition, collapse - Wise, Carol; Roett, Riordan, 1938- (Washington, D.C. : Brookings Institution Press, 2003)
Annotation Over the last twenty years Latin America has seen a definitive movement toward civilian rule. Significant trade, fiscal, and monetary reforms have accompanied this shift, exposing previously state-led economies to the forces of the market. Despite persistent economic and political hardships, the combination of civilian regimes and market-based strategies has proved to be remarkably resilient and still dominates the region. This book focuses on the effects of market reforms on domestic politics in Latin America. While considering civilian rule as a constant, the book examines and compares domestic political responses in six countries that embraced similar packages of reforms in the 1980s -- Argentina, Brazil, Chile, Mexico, Peru, and Venezuela. The contributors focus on how ambitious measures such as liberalization, privatization, and deregulation yielded mixed results in these countries and in doing so they identify three main patterns of political economic adjustment. In Argentina and Chile, theimplementation of market reforms has gone hand in hand with increasingly competitive politics. In Brazil and Mexico, market reforms helped to catalyze transitions from entrenched authoritarian rule. Finally, in Peru and Venezuela, traditional political systems have collapsed and civilian rule has been repeatedly challenged. The contributors include Carol Wise (University of Southern California), Karen L. Remmer (Duke University), Carol Graham (Brookings Institution), Stefano Pettinato (United Nations Development Programme), Consuelo Cruz (Tufts University), Juan E. Corradi (New York University), Delia M. Boylan (Chicago Public Radio), Riordan Roett (Johns Hopkins University), Martmn Tanaka(Institute for Peruvian Studies, Lima), and Kenneth M. Roberts (University of New Mexico).
Introduction: Latin American politics in the era of market reform / Carol Wise. Part One. Postreform politics: voting, mobility, and citizenship. Elections and economics in contemporary Latin America / Karen L. Remmer. Hardship and happiness: social mobility and public perceptions during market reforms / Carol Graham and Stefano Pettinato. The new Latin American citizen: first world models, third wave products / Consuelo Cruz. Part Two. Competitive elections and postreform coalition building: Argentina and Chile. Prelude to disaster: weak reform, competitive politics in Argentina / Juan E. Corradi. Taking the Concertación to task: second stage reforms and the 1999 presidential elections in Chile / Delia M. Boylan. Part Three. Politics in transition: Mexico and Brazil. Mexico's democratic transition: the search for new reform coalitions / Carol Wise. Brazil's protracted transition to democracy and the market / Riordan Roett. Part Four. Party collapse amid market restructuring: Peru and Venezuela. The political constraints on market reform in Peru / Martín Tanaka. Party system collapse amid market restructuring in Venezuela / Kenneth M. Roberts.
Includes bibliographical references (pages 273-290) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Lateinamerika; Structural adjustment (Economic policy) -- Political aspects -- Latin America; Latin America -- Economic policy; Latin America -- Economic conditions -- 1982-; Latin America -- Politics and government -- 1980-; Ajustement structurel (Économie) -- Aspect politique -- Amérique latine; Amérique latine -- Politique économique.; Amérique latine -- Conditions économiques -- 1982-; Amérique latine -- Politique et gouvernement -- 1980-; POLITICAL SCIENCE -- Political Process -- General; POLITICAL SCIENCE -- World -- Caribbean & Latin American; Economic history; Economic policy; Politics and government; Structural adjustment (Economic policy); Latin America; Demokratie; Marktwirtschaft; Structurele aanpassing (ontwikkelingseconomie); Democratisering; 83.32 economic policy; economic reform; structural adjustment; economic policy; political aspect; trend; election; social mobility; democracy; political party; Brazil; Argentina; Chile; Mexico; Peru; Venezuela (Bolivarian Republic of); réforme économique.; ajustement structurel; politique économique.; aspect politique; tendance; élection.; mobilité sociale; démocratie.; parti politique; Brésil.; Argentine; Chili; Mexique; Pérou.; Venezuela (République bolivarienne du); reforma económica.; ajuste estructural; política económica.; aspecto político.; tendencia; elección.; movilidad social; democracia; partido político.